Bahasa Inggris - Nur Malasari, Syafika; Rosdiana, Aliva (Universitas Putera Batam, 2024)
Abstract This study focuses on analyzing the expressive speech act used as conversational strategy in Ellen’s Talk Show. The strategies used are direct speech and indirect speech. The purpose of this study is to classify and to investigate the language functions of expressive speech as conversational strategy occurred in Ellen talk show entitled “Ellen Taught this Fan How to Speak English.” This study uses a qualitative method with descriptive approach in analyzing data. This study applied the theory from Searle and Vanderveken (1985) related to the type of expressive speech act. The data source is taken from a conversation between Diana Aquino as their guest and Ellen as the host. This study is a document or content analysis because the data used is from the internet and was previously posted. The technique of data analysis which the researcher used is the interactive model of Miles and Huberman for data analysis, which consisted of three steps, namely data reduction, data display, and conclusion drawing/verification. The data instrument used is utterances found in Ellen talk show. The results found 8 types of expressive language occurred involves greeting, thanking, complimenting, praising, apologizing, protesting, boasting, and complaining. Keywords: Expressive Language, Expressive Speech Act, Ellen Talk Show, Conversation’s Strategy